Effectiveness (P4K) with the Si Dora Backpack Innovation (Save Pregnant Women Movement with Blood Donor Alert) in Anticipating Pregnancy Risks at the Mantup Lamongan Health Center - Kusmiwati Kusmiwati; Heny Puji Wahyuningsih; Gunarmi Gunarmi (International Journal of Public Health, 2025)
The purpose of the study was to analyze the effectiveness of P4K with the innovation of the Dora Backpack to anticipate pregnancy risk in pregnant women in the working area of the Mantup Health Center in Lamongan Regency.This type of research is quasi-experimental with Post-test Only Control Group Design. The population of this study were pregnant women in the third trimester in the work area of the Mantup Health Center and Tikung Health Center totaling 262 pregnant women. The sampling technique is purposive sampling. The number of samples was 176 pregnant women, consisting of 88 control pregnant women and 88 intervention pregnant women. Univariate data analysis with frequency distribution table, bivariate analysis with Mann Withney and Logistic Regression. Based on the results of the Mann Withney test in the control and intervention groups, ap value of 0.000 means that P4K with the Si Dora Backpack Innovation is effective in increasing the ability of pregnant women to anticipate the risk of pregnancy and based on the results of the Logistics Regression test, external variables do not affect the ability to anticipate pregnancy risk factors, namely age with p value 0.341, education with p value 0.587, and occupation with p value 0.631. P4K With Si Dora's Backpack Innovation is effective in increasing the ability of pregnant women to anticipate the risk of pregnancy.